Panax notoginseng Saponins for Treating Coronary Artery Disease: A Functional and Mechanistic Overview - Duan, Lian; Xiong, Xingjiang; Hu, Junyuan; Liu, Yongmei; Li, Jun; Wang, Jie (Frontiers in Pharmacology, 2017)
Coronary artery disease (CAD) is a major public health problem and the chief cause of morbidity and mortality worldwide. Panax notoginseng, a valuable herb in traditional Chinese medicine (TCM) with obvious efficacy and favourable safety, exhibits a great promise as a novel option for CAD and is increasingly recognized clinically. Firstly, this review introduced the mechanisms of panax notoginseng and panax notoginseng saponins (PNS), which can regulate signalling pathways associated with inflammation, lipid metabolism, the coagulation system, apoptosis, angiogenesis, atherosclerosis and myocardial ischaemia. Secondly, recent clinical trials on treatment with PNS either alone or in combination with conventional drugs are considered as novel treatment strategies.